OPTIMALISASI KONDISI AMOBILISASI GLUKOMINASE MENGGUNAKAN PADATAN PENDUKUNG BENTONIT BENTUK ION UNTUK KONVERSI PATI MENJADI GULA - Afaf Baktir; Sri Sumarsih; Hamami (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 1995)
Bentonit is a clay available in a lot of quantity and very chief. It can be activated to cation or anion exchanger like resin. His research was done in order to search a treatment and to get optimum condition for binding the glucoamylase to the bentonit, and to observe the ability of immobilized glucoamylase obtained in hydrolyzing amylum. It was done three ways to activate the bentonit, to obtain three kinds of bentonit, those are 'active bentonit' (adsorbs enzyme physically) and 'cation exchanger bentonit' consist B- NH4+, and B-H+ (bind enzyme ionically). The bentonit was contacted to glucoamylase in various condition to search the optimum condition (pH, concentration, temperature, and contact duration time). Immobilized glucomynase obtained was tested it's binding strengthness and the ability of hydrolyze amylum to glucose. The conclusion of this research were, (1) bentonit can be used as a supporting material for immobilizing glucomynase in the form of B-H+ cation exchanger, (2) the optimum condition of bentonit and glucomylase binding was in pH = 5.5 and at 25oC, contact duration time was 30 minutes, (3) immobilizes glucomylase column (height of 1 cm and diameter of 2.5 cm) had conversion ability at the level of 19.88%.